2021
DOI: 10.1111/tbed.14242
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of African swine fever virus to HEK293T cells

Abstract: African swine fever (ASF), caused by African swine fever virus (ASFV), is a highly contagious disease with high morbidity and mortality in domestic pigs. Although adaptation of ASFV to Vero cells has been investigated, the phenotypic changes and the corresponding genomic variations during adaptation of ASFV to other cell lines remain unclear. To obtain a cell‐adapted ASFV strain, different cell lines were tested to determine whether they support ASFV infection. Interestingly, the ASFV wild‐type strain ASFV‐HLJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 44 publications
1
66
0
Order By: Relevance
“…We further explored the subcellular localization of pH240R in HEK293T cells infected with the HEK293T-adapted ASFV (ASFV-P31) ( 22 ) by confocal microscopy. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We further explored the subcellular localization of pH240R in HEK293T cells infected with the HEK293T-adapted ASFV (ASFV-P31) ( 22 ) by confocal microscopy. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PAMs ( 22 ) and HEK293T cell lines, which were derived from our own stock stored in liquid nitrogen, were cultured with RPMI 1640 medium (catalog no. C11875500BT; Gibco) supplemented with 10% heat-inactivated fetal bovine serum (FBS) (catalog no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this discovery brings hope to the large-scale production of the ASF vaccine in cell lines, the safety and genetic stability of the ASFV-G-ΔI177L/ΔLVR strain still needs further evaluation. Furthermore, we recently demonstrated that ASFV adapted to HEK293T cells with deletion of the left-end variable MGF genes [ 18 ]. The deletion of MGF300 ( 1L , 2R , and 4L ) and MGF360 ( 8L , 9L , 10L , and 11L ) genes might be important for the adaptation of ASFV to HEK293T cells at the early stage [ 18 ].…”
Section: Strategies For Generating Asf Lav Candidatesmentioning
confidence: 99%
“…Furthermore, we recently demonstrated that ASFV adapted to HEK293T cells with deletion of the left-end variable MGF genes [ 18 ]. The deletion of MGF300 ( 1L , 2R , and 4L ) and MGF360 ( 8L , 9L , 10L , and 11L ) genes might be important for the adaptation of ASFV to HEK293T cells at the early stage [ 18 ]. Moreover, the pathogenicity and immunogenicity of the HEK293T cell-adapted ASFV will be evaluated in pigs.…”
Section: Strategies For Generating Asf Lav Candidatesmentioning
confidence: 99%